Structural Evolution of Basaltic Melts in the Deep Earth: Insights From High‐Pressure Sound Velocity of Glass - Trubowitz, Charlotte; Murakami, Motohiko; Petitgirard, Sylvain; Liebske, Christian; McCammon, Catherine (Journal of geophysical research. Solid earth, 2024)
The densification mechanisms of silicate melts under high pressure are of key interest in understanding the evolution of the early Earth and its present‐day internal structure. Here, we report Brillouin spectroscopy‐derived transverse acoustic wave velocities VS $\left(V_{S}\right)$ from a basaltic glass at high pressures up to 163 GPa and ambient temperature to provide insight into pressure‐induced changes in its elasticity and, by extension, its density. We find that the pressure dependence of VS ${V}_{S}$ below 110–140 GPa follows a trend nearly tantamount to those of pyrolite and Fe‐ and (Fe,Al)‐bearing MgSiO3 glasses, indicating that the large compositional differences among these glasses do not exert variable acoustic wave velocity trends. However, at higher pressures we observe a small departure from the VS ${V}_{S}$ profiles of the Al‐poor compositions toward higher acoustic wave velocities to eventually become stiffer. This pressure‐induced steepening in VS ${V}_{S}$ is comparable to that of (Mg, Fe, Al)(Si, Al)O3 glass, and suggests a possible structural change toward a denser state caused by more rapidly changing Al–O coordination in network‐forming Al. Coupled with the high Fe content in basalt, this may render basaltic melt denser than surrounding minerals in the deep lower mantle, and may provide an additional mechanism for the existence of ultralow‐velocity zones. Plain Language Summary Silicate melts are subject to different densification mechanisms from the counterpart solids. Although less dense at ambient/low pressures and for most of the mantle, it has long been speculated that at high enough pressures a density inversion may take place, where melts may become denser than the corresponding solids. This would have profound implications for the present‐day structure and dynamics of the Earth and its evolution through geological history. We have experimentally measured the sound wave velocities of a basaltic glass, which serves as a laboratory analogue to melt, up to 163 GPa. Through comparison of our sound wave velocity‐pressure profile to other glass compositions we observe a slight deviation in steepness above 110–140 GPa to a potentially stiffer and denser state. This pressure‐induced change may be the result of changes in the Al–O coordination environment. Extrapolated onto expected melt compositions in the lower mantle, which are enriched in both Al and heavy Fe, this may render dense pools of silicate melt gravitationally stable at the bottom of the mantle. Key Points We have carried out acoustic wave velocity measurements of a basaltic glass up to 163 GPa The VS‐pressure profile of basalt shows close similarities to other, more depolymerized glasses up to 110–140 GPa, where it becomes steeper This anomaly is likely induced by changes in Al–O coordination